1980
DOI: 10.1128/aac.17.5.770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ribavirin on respiratory syncytial virus in vitro

Abstract: Ribavirin was demonstrated to have an antiviral effect on respiratory syncytial virus in vitro. A 50% reduction in plaque number was observed at concentrations of 3 to 10 Ag of ribavirin per ml. This effect was observed when the drug was added as late as 12 h postinfection. At concentrations of greater than 10 ,ug of ribavirin per ml, the size of the syncytial plaque also noticeably decreased. Ribavirin similarly decreased the number of infectious units released into the culture supernatant. The antiviral effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 17 publications
6
46
1
1
Order By: Relevance
“…Others have shown that continuous exposure of airway cells to ribavirin for up to 1 week produces no detectable toxicity as measured by cell growth or release of lactate dehydrogenase into the culture medium (21,35). Our microarray data are consistent with these findings in that ribavirin treatment alone has only minor effects on epithelial gene expression, influencing the expression of only 31 genes (by twofold or less, ca.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Others have shown that continuous exposure of airway cells to ribavirin for up to 1 week produces no detectable toxicity as measured by cell growth or release of lactate dehydrogenase into the culture medium (21,35). Our microarray data are consistent with these findings in that ribavirin treatment alone has only minor effects on epithelial gene expression, influencing the expression of only 31 genes (by twofold or less, ca.…”
Section: Discussionsupporting
confidence: 81%
“…In RSV-infected epithelial cells, ribavirin reduces plaque formation, the release of infectious virions, and F glycoprotein expression in a dose-dependent manner over the range of 10 to 100 g/ml without cellular toxicity in culture for up to 7 days (21,35). To determine the optimal concentration and timing of ribavirin treatment for the inhibition of viral transcription for our studies, A549 monolayers pretreated (2 h) or posttreated (1 h) with increasing concentrations of ribavirin were exposed to pRSV.…”
Section: Resultsmentioning
confidence: 99%
“…Hruska et al (17) reported an ED50 of 3 to 10 ,ug/ml for the inhibition of RSV plaque formation by ribavirin. In our assays, ribavirin exhibited an ED50 of 2.8 ,.ug/ml for the Long strain of RSV and an average ED50 of 5.8 ,ug/ml for eight different strains of RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of ribavirin in infants had marginal effects in reducing the need for mechanical ventilator support and the duration of hospitalization following hRSV infection, whereas its anti-hRSV effect has been clearly established in vitro and in a rodent model. [8][9][10] Thus, continuing efforts are needed to discover new agents that can prevent or treat hRSV infection. Xylitol is a well-known sugar substitute with the formula (CHOH) 3 (CH2OH) 2 .…”
mentioning
confidence: 99%